Waxing into words: Virginia Woolf and the Westminster Abbey funeral effigies - Kore Schroder, Leena (Rohnert Park, Calif, 2013)
This articles derives its methodology from an analysis of the figures in the historical collection of royal funeral effigies in Westminster Abbey, London. As historical representations these resist categorisation: are they to be read as human and profane, or idealized and sacred; are they authorized, or carnivalesque history; are they fiction or fact? These effigies make official history disturbingly strange even as they appeal to us at the level of bodily familiarity. The Abbey wax figures fascinated Virginia Woolf throughout her life and make multiple cameo appearances in her work. The article centres on the historiographical strategies of her 1928 essay, ‘Waxworks at the Abbey’, in order to show how Woolf reconfigures history in ways which anticipate its ultimate embodiment in the character Eliza Clark in the 1941 Between the Acts. With her ‘pearl-hung’ head, ‘shiny satins’ and ‘sixpenny brooches’, Eliza is both everyday shopkeeper and yet another waxwork dummy of Elizabeth I, inhabiting that borderland where what is most ordinary suddenly becomes the uncanny.